Carbohydrate utilization by enterohaemorrhagic Escherichia coli O157:H7 in bovine intestinal content. (6th November 2012) - Bertin, Yolande; Chaucheyras‐Durand, Frédérique; Robbe‐Masselot, Catherine; Durand, Alexandra; de la Foye, Anne; Harel, Josée; Cohen, Paul S.; Conway, Tyrell; Forano, Evelyne; Martin, Christine
Summary: The bovine gastrointestinal (GI) tract is the main reservoir for enterohaemorrhagic Escherichia coli (EHEC) responsible for food‐borne infections. Characterization of nutrients preferentially used by EHEC in the bovine intestine would help to develop ecological strategies to reduce EHEC carriage. However, the carbon sources that support the growth of EHEC in the bovine intestine are poorly documented. In this study, a very low concentration of glucose, the most abundant monomer included in the cattle dietary polysaccharides, was detected in bovine small intestine contents (BSIC) collected from healthy cows at the slaughterhouse. Six carbohydrates reported to be included in the mucus layer covering the enterocytes [galactose, N ‐acetyl‐glucosamine (GlcNAc), N ‐acetyl‐ galactosamine (GalNAc), fucose, mannose and N ‐acetyl neuraminic acid (Neu5Ac)] have been quantified for the first time in BSIC and accounted for a total concentration of 4.2 mM carbohydrates. The genes required for enzymatic degradation of the six mucus‐derived carbohydrates are highly expressed during the exponential growth of the EHEC strain O157:H7 EDL933 in BSIC and are more strongly induced in EHEC than in bovine commensal E. coli . In addition, EDL933 consumed the free monosaccharides present in the BSIC more rapidly than the resident microbiota and commensal E. coli, indicating a competitive ability of EHEC to catabolize mucus‐derived carbohydrates in the bovine gut. Mutations of EDL933 genes required for the catabolism of each of these sugars have been constructed, and growth competitions of the mutants with the wild‐type strain clearly demonstrated that mannose, GlcNAc, Neu5Ac and galactose catabolism confers a high competitive growth advantage to EHEC in BSIC and probably represents an ecological niche for EHEC strains in the bovine small intestine. The utilization of these mucus‐derived monosaccharides by EDL933 is apparently required for rapid growth of EHEC in BSIC, and for maintaining a competitive growth rate as compared with that of commensal E. coli . The results suggest a strategy for O157:H7 E. coli survival in the bovine intestine, whereby EHEC rapidly consumes mucus‐derived carbohydrates that are poorly consumed by bacteria belonging to the resident intestinal microbiota, including commensal E. coli .